2018
DOI: 10.1088/1674-1056/27/9/097303
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of H/O trapping and clustering on U/Al interface

Abstract: Al coating on U surfaces is one of the methods to protect U against environmental corrosion. The behaviors of hydrogen and oxygen impurities near the Al/α-U interface have been studied in the density functional theory framework. It turns out that U vacancies tend to segregate to the interface with segregation energies of around 0.5-0.8 eV. The segregated U vacancy can act as a sink for H and O impurities, which is saturated when filled with 8 H or 6 O atoms, respectively. Moreover, the O impurities tend to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Among the actinide elements, Th, U, and the transuranium elements of Np, Pu, Am and Cm have important applications and have been synthesized in appreciable quantities in nuclear reactors. [1][2][3] The other actinides are mostly used for research. Most of them are radioactive.…”
Section: Introductionmentioning
confidence: 99%
“…Among the actinide elements, Th, U, and the transuranium elements of Np, Pu, Am and Cm have important applications and have been synthesized in appreciable quantities in nuclear reactors. [1][2][3] The other actinides are mostly used for research. Most of them are radioactive.…”
Section: Introductionmentioning
confidence: 99%
“…Akshaya et al [76] studied the interaction energy of atomic defects in bcc iron, their relevant results are compared with our investigations. Ouyang et al [77] reported that the segregated U vacancy on U/Al interface can act as a sink for H and O impurities. Studied in our previous work were the interactions of La-C/N, [78] La-FSA (here FSA stands for foreign substitutional atom, i.e., Al, Si, Ti, V, Cr, Mn, Co, Ni, Cu, Nb or Mo), [79] C/N-FSA, [80] C-N, and C-N-vacancy [81] in bcc Fe.…”
Section: Introductionmentioning
confidence: 99%
“…The photoinduced magnetic processes have been directly observed using time-resolved Lorentz TEM imaging. Very recently, the nonequilibrium phase transition between CDW states and the relevant hidden quantum states has been carefully investigated and analyzed in low-dimensional system 1T-TaS2−xSex at low temperatures [14,15,16].…”
mentioning
confidence: 99%